The Relationship Between Household Credit and Banking Stability in Malaysia: Panel Evidence - NURHUDA NIZAR; Zulkefly Abdul Karim (Gadjah Mada International Journal of Business, 2021)
This study investigates the relationship between household credit and banking stability in Malaysia using a sample of 37 commercial banks spanning the period from 2008 to 2015. In analyzing household credit’s influence on the Malaysian banking sector’s stability, household credit was categorized into two components, namely mortgage and consumer credit. The Banking Stability Index (BSI) for each bank is constructed using 15 bank-specific variables and some macro-economic variables. The determinants of the BSI are estimated using a static panel data technique. The fixed-effects regression results showed a statistically significant negative relationship between both forms of household credit (mortgage credit and consumer credit) upon the banking sector’s stability. The finding signals that understanding the link between household credit and the Bank Stability Index is crucial to the policymakers and the banks’ management in closely monitoring household credit, particularly mortgage and consumer credit.